HIV-RELATED STIGMA, DISCRIMINATION AND COPING STRATEGIES AMONG PEOPLE LIVING WITH HIV/AIDS RECEIVING TREATMENT AT THE UNIVERSITY COLLEGE HOSPITAL, IBADAN, NIGERIA (2014)
Stigma complicates the prevention and control of HIV worldwide as it adversely affects the care seeking practices among People Living With HIV/AIDS (PLWHA). In Nigeria HIV stigma-related practices experienced by PLWHA have not been adequately investigated. This study therefore focused on HIV-related stigma, discrimination and coping mechanisms among PLWHA receiving treatment at the University College Hospital (UCH), Ibadan, Nigeria. The study was a cross-sectional survey. Systematic random sampling technique was used to select 700 consenting clients at President Emergency Plan for AIDS Relief clinic UCH. A semi-structured questionnaire which included questions on stigma-related and discriminatory experiences, perceived consequences and coping strategies was used for data collection. Indepth Interviews (IDI), were conducted among eight consenting respondents who had experienced serious HIV-related stigma and discrimination such as loss of job, divorce and marital separation. Quantitative data were analyzed using descriptive statistics and Chi-square test. Qualitative data were analysed using thematic approach. Respondents’ mean age was 40.0 ± 9.4 years, 60.8% were married, 67.7% were females, and 56.2% were traders. Majority (78.1%) had ever experienced self-stigmatization as a result of their HIV sero-positive status with 27.0% experiencing it within the three months preceding the study. A major indicator of self-stigmatization was the unwillingness to disclose HIV sero- positive status to family members (53.7%) and to friends (69.3%). Significantly more females (56.3%) than males (48.7%) were scared of disclosing their HIV positive status to family members (p<0.05). Nearly a third of respondents (30.3%) had ever experienced stigmatization from other people. Stigmatization experienced by PLHWA included treatment with disdain (67.0%) and restriction of social interaction (65.9%). Few (5.1%) respondents experienced at least one form of discrimination in the three months preceding the study. The experienced discriminatory acts included rejection by friends (1.3%), avoidance (1.7%), isolation (1.1%), gossips by members of the community (0.6%), loss of job (1.3%) and disclosure of status to others by health workers without permission (4.0%). The perceived consequences of HIV-related stigma included sadness (68.0%), divorce (61.3%) and social isolation (58.9%). The coping strategies adopted by respondents included being unperturbed (53.7%), praying (45.9%) and ignoring acts of stigmatization (40.0%). Only 27.7% of respondents enrolled with a social support group for PLWHA. The most common benefits of being a member of a support group included sharing of discriminatory experiences (29.8%), counselling services (29.8%), sharing of condom (22.0%), other material support (18.4%) and acquisition of enterpreneurial skills (1.2%). Verbal assault was a key concern among majority of Indepth Interviewees. In addition, marital instability was disclosed to be a major social consequence of HIV among married persons. Stigmatization and discrimination constitute major challenges among the People Living With HIV and AIDS. Psychotherapy, advocacy and public enlightenment are needed to address the problems.